The RAD51C exonic splice-site mutations c.404G>C and c.404G>T are associated with familial breast and ovarian cancer. Issue 2 (March 2017) - Neidhardt, Guido; Becker, Alexandra; Hauke, Jan; Horváth, Judit; Bogdanova Markov, Nadja; Heilmann-Heimbach, Stefanie; Hellebrand, Heide; Thiele, Holger; Altmüller, Janine; Nürnberg, Peter; Meindl, Alfons; Rhiem, Kerstin; et al.
Abstract : Whereas RAD51C mutations increase the relative risk for ovarian cancer (OC) to 5.88 (95% confidence interval=2.91–11.88, P =7.65×10 –7 ), the associated risks for breast cancer (BC) remain largely unknown, as deleterious RAD51C alterations are extremely rare in BC-only families. Here, we report the results of a RAD51C mutational screening in a large series of German familial index patients negative for pathogenic BRCA1/2 mutations and the in-vitro characterization of two novel exonic RAD51C splice-site mutations. A total of 610 index cases derived from BC/OC ( n =587) or OC-only families ( n =23) were screened for potentially deleterious germline mutations in RAD51C . The frequencies of two splice-site mutations were assessed by single-nucleotide polymorphism genotyping in 1410 additional cases not enriched for OC family history. In three independent families, we identified novel splice-site mutations affecting the last nucleotide of exon 2 (c.404G>C, c.404G>T). Both mutations disrupt proper RAD51C pre-mRNA processing and cause a missense substitution immediately followed by a stop codon (p.Cys135Serfs*2; p.Cys135Leufs*2). Even though both mutations have similar effects on the protein level, they are associated with either BC/OC, OC-only, or BC-only family histories. The rare finding of a clearly truncating RAD51C mutation in an early-onset BC patient with a BC-only family history supports the notion that compromised RAD51C function may result in both BC and OC. Large international collaborative studies are needed to quantify the relative risk of RAD51C alterations for BC and to unravel the genetic modifying factors that determine phenotypic variability with respect to cancer site.